Quality of life, fatigue, depression, attention deficits, and pain after childhood Langerhans cell histiocytosis - Malin Sveijer; Désirée Gavhed; Helena Hertzberg; Eric Zander; Jan-Inge Henter; Tatiana von Bahr Greenwood (Blood Neoplasia)
Abstract: Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplasia with variable clinical presentation, ranging from self-healing single lesions to multisystem, potentially fatal disease. Long-term consequences, including progressive central nervous system (CNS) neurodegeneration, are common. In this cross-sectional postal survey, we investigated how LCH affects long-term everyday life. All individuals aged ≥10 years diagnosed with LCH in childhood ≥5 years ago in Stockholm from 1990 to 2014 were invited to participate. Thirty-two of 61 eligible individuals (52%) answered questionnaires assessing health-related quality of life (HRQOL), fatigue, pain, depression, and attention deficits. Their median postdiagnosis time was 19.4 years. Overall, 14 of 32 (44%) had had multisystem disease, including 4 (12%) with risk organ involvement, and 17 of 32 (53%) had received systemic treatment. Five (16%) had CNS involvement, all with neurodegeneration. The mean total HRQOL score was 78.8 and the mean total fatigue score 68.7 (Pediatric Quality of Life Inventory). Five (16%) reported a diagnosed neurodevelopmental disorder. In patients aged ≥15 years, 42% reported long-lasting pain, and 27% had scores indicating depression. Poorer HRQOL correlated with fatigue and symptoms of depression and attention deficits. Patients with single-system disease and patients with multisystem disease with the longest duration of systemic treatment reported the best HRQOL. We conclude that patients with childhood LCH report high frequencies of fatigue, long-lasting pain, and symptoms of depression and attention deficit in the long term, which are associated with poorer quality of life and should be evaluated at follow-up. We also raise the question of whether longer treatment may reduce long-term consequences and have a positive impact on perceived quality of life.